Implementation of Speed Measurement and Speed Limit System on Motorcycles Based on Global Positioning System - Nisa, Fidyatun; Aulia, Muhammad Haiqal (Internet of Things and Artificial Intelligence Journal, 2024)
The Indonesian National Police Traffic Corps (Korlantas Polri) recorded many traffic accidents in 2022, with hundreds of lives lost. High riding speed was identified as a contributing risk factor to these accidents. Uncontrolled motorcycle conditions and the lack of rider focus while riding were also identified as potential causes of accidents. Therefore, researchers designed a solution by creating a device to address these issues. The device to be discussed here is a GPS-based speed-measuring and limiting device. This device aims to reduce the risk of accidents by controlling riding speed. The speed sensor utilizes GPS, with the function to temporarily stop the motorcycle when it reaches a speed of 48 km/h, preventing riders from riding at high speeds. The speed limitation at 48 km/h is expected to reduce the risk of traffic accidents. Based on the analysis and calculations of this GPS-based motorcycle speed-limiting device, it is ensured that the motorcycle will not be damaged when the ignition coil is disrupted for 1 second to temporarily turn off the motorcycle upon reaching the specified speed.